1993
DOI: 10.1002/app.1993.070471213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high‐energy radiation on the surface chemistry of polystyrene: A mechanistic study

Abstract: SYNOPSISIrradiation of polystyrene by 15 Mrad gamma or exposure to a 254 nm ultraviolet (UV) light source leads t o surface oxidation of the polymer to depths greater than 10 nm as opposed to -3 nm depth offered by either plasma or corona-discharge treatment. Oxidation increases linearly with UV irradiation time. More carboxyl (0 = C -0) acid functionality, which increases with depth, was detected for UV-treated polymer. With 3 Mrad gamma irradiation, only hydroxyl (C -0) groups were detected by XPS as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 9 publications
1
46
0
Order By: Relevance
“…The surface chemical compositions of the polymer surfaces have been characterized using a Kratos Axis HSi 5 channel-imaging x-ray photoelectron spectrometer using monochromated Al K˛radiation (1486.6 eV) operated at 150 W in a residual vacuum of <4 ð 10 9 Torr with the analyser in fixed transmission mode. Charge neutralization was used for all samples with the standard operating conditions for insulator surfaces: 2.8 V bias voltage; 1.0 V electron filament voltage; C1.9 A filament current.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface chemical compositions of the polymer surfaces have been characterized using a Kratos Axis HSi 5 channel-imaging x-ray photoelectron spectrometer using monochromated Al K˛radiation (1486.6 eV) operated at 150 W in a residual vacuum of <4 ð 10 9 Torr with the analyser in fixed transmission mode. Charge neutralization was used for all samples with the standard operating conditions for insulator surfaces: 2.8 V bias voltage; 1.0 V electron filament voltage; C1.9 A filament current.…”
Section: Methodsmentioning
confidence: 99%
“…radiofrequency (r.f.) 7 and remote plasmas, 8 gamma irradiation 9 and electron beam modification. 10 A common problem with these methods is that reproducibility and control may not be simple.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of polymer surfaces based on physical or chemical methods including those employing plasma [1][2][3][4][5][6][7], corona discharge [8][9][10][11], ultraviolet (UV) light [7,[10][11][12], ion beams or bombardment [13][14][15], γ -radiation [16][17][18], or chemical solutions [19][20][21] has been widely performed in order to improve macroscopic surface properties such as wettability, chemical reactivity, printability, biocompatibility, and coating adhesion. In most cases, the hydrophobic polymer surface becomes highly hydrophilic due to the formation of oxygen-containing functional groups on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the hydrophobic polymer surface becomes highly hydrophilic due to the formation of oxygen-containing functional groups on its surface. However, it has been reported that the quantity and distribution of such moieties, along with the degree of hydrophilicity of the modified surface, are extremely sensitive to the modification method, experimental parameters, and materials employed [7,17,22]. For example, Onyiriuka [17] has demonstrated the surface modification of polystyrene (PS) using γ -rays, 254-nm UV light, O 2 plasma, X-rays, or corona discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modifications of polymer surfaces have been widely performed using plasma, [10][11][12][13][14][15] corona discharge, 16,17 ultraviolet (UV) light, 17,18 ion beams 19 or bombardment, [20][21][22] g-radiation, [23][24][25] and chemical solutions [26][27][28] to modify macroscopic surface properties, such as wettability, friction, adhesion, biocompatibility, molecular recognition and LC alignment. In most cases, the formation of oxygen-containing functional groups, such as -OH and -COOH, occurs on the polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%